The Influence Of Innovation And Collaboration On Improving Public Service Performance At Balai Kekarantinaan Kesehatan Kelas I Tanjungpinang - Jubaidillah, Jubaidillah; Putri, Ratna Komala (UNIVERSITAS PAKUAN, 2025)
Based on the results of the Corruption Free Zone assessment in BKK Tanjungpinang over the last three years, significant improvements are evident in several components, such as Change Management and Management. However, components of Public Services consistently receive low scores, particularly in 2021, with a further decrease observed in 2023. Additionally, the assessment of employee performance in providing services in 2024 reveals categories other than excellent, including good and average.. This study aims to determine and analyze innovation, collaboration, work flexibility and service performance at BKK Tanjungpinang, to determine and analyze the effect of innovation, the effect of collaboration on service performance and This research adopts a quantitative approach by utilizing questionnaires and literature studies as data collection methods. The sampling technique used is probability sampling, which includes six Work Teams (Timker) within the agency. To analyze the data, this study used the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach. The findings of this study reveal that innovation is in a very high category, collaboration is very effective and public service performance is in a very good category. Based on the results of correlation analysis between variables, it can be concluded that the variables of innovation, collaboration, and work flexibility are empirically proven to have an effect on improving public service performance. Simultaneously, the variables of innovation and collaboration, contribute significantly to improving the performance of public services in BKK Tanjungpinang.